Development of an experimental 3-D tool based on radiochromic films to determine normal tissue doses in external radiotherapy. (August 2019) - Colnot, J; Garnier, G; Zefkili, S; Dumas, J-L; Gschwind, R; Huet, C
Abstract: External radiotherapy largely proved its efficacy to treat cancer. However, this technique leads to unavoidable exposure of normal tissues that may results in adverse effects. One of the main concerns is the induction of second cancers that may appear at the periphery or even away from the treated area. Risk estimation models need accurate 3-D dosimetric data on healthy organs. To this aim, we developed an experimental tool based on radiochromic films measurements. In this work, we present a study performed with a heterogeneous phantom. EBT3 films were positioned in between the phantom slices and irradiated according to a VMAT plan. The dose was reconstructed in 3-D by interpolation thanks to an in-house Matlab tool. Two interpolation methods are studied and the reconstructed dose is compared to independent film measurements for validation. Finally, dosimetric data such as DVH are compared to the TPS evaluation. Continuous interpolation proves to better reconstruct the doses in high gradient areas whereas linear interpolation seems to be a better option to evaluate doses away from the field edge. Besides, TPS and 3-D measurements give comparable results for organs placed inside the beams (maximum 6.3% difference on organs mean doses). However, the TPS tends to underestimate doses to organs placed at least partially outside the fields (from 29 to 59% difference on mean doses). Optimization of the dose reconstruction tool by using a combination of the two interpolation methods is ongoing. Comparison with gel dosimetry will also be investigated.